General and Statistical Thermodynamics - Tahir-Kheli, Raza (Graduate Texts in Physics, 2012)
This textbook explains completely the general and statistical thermodynamics. It begins with an introductory statistical mechanics course, deriving all the important formulae meticulously and explicitly, without mathematical short cuts. The main part of the book deals with the careful discussion of the concepts and laws of thermodynamics, van der Waals, Kelvin and Claudius theories, ideal and real gases, thermodynamic potentials, phonons and all the related aspects. To elucidate the concepts introduced and to provide practical problem solving support, numerous carefully worked examples are of great value for students. The text is clearly written and punctuated with many interesting anecdotes. This book is written as main textbook for upper undergraduate students attending a course on thermodynamics.